The effects of iron deficiency on infants' developmental test performance - SAVE, DİLŞAD; AKMAN, MEHMET (TAYLOR & FRANCIS AS, 2004)
Aim: To assess the effects of iron deficiency on developmental test scores in infants. Methods: This prospective, single-blind, controlled clinical intervention study was made on 108 children aged 6-30 mo who applied to our paediatric outpatient clinic. The cases were classified as control (n = 31, haemoglobin greater than or equal to11 g/dl, serum ferritin > 12 mug/l, MCV greater than or equal to70 fl), non-anaemic iron deficiency (NAID, n = 40, haemoglobin greater than or equal to 11 g/dl, serum ferritin less than or equal to 12 mug/l, MCV greater than or equal to70 fl) and iron deficiency anaemia (IDA, n = 37, haemoglobin <11 g/dl, ferritin &LE; 12 μg/l, MCV <70 fl) due to their anaemia status. In each group, MCV, haemoglobin and ferritin levels were measured, and Denver Developmental Screening Test (DDST) and Bayley Scales of Infant Development (BSID-I) were administered before and after a 3-mo follow-up. IDA and about half of the NAID subjects were treated with oral iron for 3 mo. Results: Subjects with iron deficiency showed significantly lower developmental test scores both with BSID-I and DDST-II compared to their iron-sufficient peers (p < 0.05). After 3 mo of iron treatment, lower mental developmental test scores were no longer observed among the IDA and NAID groups whose anaemia and iron deficiency were also corrected. No significant differences were found between control NAID and control IDA groups on DGTT-II results after treatment. The difference in motor and mental developmental scores did not appear to depend on environmental and family factors considered in the analyses. Conclusion: These findings support the conclusions that iron deficiency may cause lower mental I and motor test scores in infants and these adverse effects can be improved by iron therapy.
Keywords: anaemia; infant; iron deficiency; mental development; motor development; PSYCHOMOTOR DEVELOPMENT; ANEMIA; THERAPY; BEHAVIOR; SCORES